Evaluating the usability of interactive infographics for raising tuberculosis awareness among UiTMCK students / Wan Salfarina Wan Husain and Siti Hasrinafasya Che Hassan - Wan Husain, Wan Salfarina; Che Hassan, Siti Hasrinafasya (Universiti Teknologi MARA, Kelantan, 2023)
One of the sustainable development goals (SDGs) is related to good health and well-being. By 2039, one of the issues that wants to be solved is tuberculosis. Due to the ease of tuberculosis infection, anyone can be exposed to this disease. Lack of knowledge and low awareness about this disease can bring more critical consequences. Therefore, interactive infographics were used since they have the power to visualize content and they became popular on digital and social media platforms. Yet, only a few studies investigated the impact of design on target users. This paper presents the design and development of an infographic-based ADDIE model instructional design on health education that focuses on tuberculosis awareness. Creating an interactive awareness platform is a great idea which is suitable for the educational environment in conveying the idea through media social. The purpose of this study was to evaluate the usability of interactive infographic awareness on tuberculosis among 90 UiTM students. The results from the System Usability Scale (SUS) assessment indicated that the use of an interactive infographic for tuberculosis awareness is a successful platform, achieving a 'Good' rating with a score of 78.